1. ## Solving Linear Equations

What is the answer for this and how do yo uget it?

I initially thought this would be fairly simple but i got x=35/6 rather than the answer, which was 1 and 7/11.

2. I would begin by causing each term to have the same denominator.

This will change up some of the numerators. Show us some steps so we can help you catch the problem.

3. Originally Posted by prettiestfriend
What is the answer for this and how do yo uget it?

I initially thought this would be fairly simple but i got x=35/6 rather than the answer, which was 1 and 7/11.
NOTE, IF THE LAST NUMERATOR DOES NOT SAY 8x-2x, THEN THIS IS NOT THE ANSWER!!! I thought it said 8x-2x so i went with that...

For this problem, you have to get all of the denominators to be the same, so you have to multiply each equation by a specific number so that each denominator will have a most common multiple. In this case, I think it is safe to say that the common denominator should be 36, meaning that the equation should be this after simplification:

(24x-30)-(18x+45)=32x-8x

Now just solve for x...

24x-18x-30-45=24x
-75=18x
x=(-25/6)

Hope this is right, but the equation did not come out really clear on my computer, but I hope I helped

4. Sorry the last bit is (8x/9) -2x

What I did was multiply everything by 36.

So it became

6(4x-5) - 9（-2x+5) = 4(8x) - 36(2x)

and then worked it out from there

5. Originally Posted by prettiestfriend
Sorry the last bit is (8x/9) -2x

What I did was multiply everything by 36.

So it became

6(4x-5) - 9（-2x+5) = 4(8x) - 36(2x)

and then worked it out from there
OK...

That changes it then....

(24x-30)-(18x+45)=32x-72x

Now just solve for x...

24x-18x-30-45=-40x
-75=-46x
x=(75/46)

I think this is the right answer...I have a monster headache after today =[

6. Either the answer in the back of the book is wrong, or the problem was copied down wrong. I plugged in x = 1 and it is not a solution.

\begin{aligned}
\frac{4x - 5}{6} - \frac{2x + 5}{4} &= \frac{8x}{9} - 2x \\
\frac{4 - 5}{6} - \frac{2 + 5}{4} &= \frac{8}{9} - 2 \\
-\frac{1}{6} - \frac{7}{4} &= \frac{8}{9} - 2 \\
-\frac{6}{36} - \frac{63}{36} &= -\frac{10}{9} \\
-\frac{69}{36} &\neq -\frac{40}{36} ???
\end{aligned}

01